The Effectiveness of Eazy Passport Innovation in Passport Issuance Services in Class 1 Immigration Offices, Samarinda City - Deandlles Christover; Juniati Bilung (Budapest International Research and Critics University, 2022)
This study aims to find out how effective the innovation of the Eazy Passport service at the Immigration Office Class I Samarinda is in providing passport issuance services and seeks to find out the supporting factors and inhibiting factors for passport issuance services and find solutions offered so that they can be input for related parties to make the service available. Eazy Passport is better in later implementations. This study is a qualitative descriptive study with the aim of explaining the effectiveness of the Eazy Passport innovation in providing passport issuance services at the Class 1 Immigration Office of Samarinda City. Data were collected through the process of interview, observation, and literature study. The results of this study are immigration efforts in improving immigration services and the impact resulting from the implementation of the Eazy Passport service in immigration services. Immigration has carried out and will continue to innovate in order to realize integrated public services. The existence of a pandemic has an impact on government agencies which results in a decrease in the intensity of the services provided. Every Immigration Office in Indonesia has made various efforts to improve the quality of its services with an integrated service system. The Eazy Passport service is a policy issued by the Directorate General of Immigration that aims to increase the number of passport and PNBP issuances produced by each Immigration Office. The implementation of the Eazy Passport service allows passport application activities to be carried out flexibly and practically. This activity was carried out in accordance with the mapping of the work area of each Immigration Office while still implementing health protocols to prevent the transmission of Covid-19.